Keunggulan Dan Ketangguhan Ideologi Pancasila - Surajiyo, Surajiyo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
Ideology actually comes from a philosophical system, and is the implementation of a philosophical system. Communism originated in the philosophy of materialism, gave birth to atheism and class struggle and the dictatorship of the proletariat. Pancasila originates from the philosophy of the Indonesian nation itself since time immemorial in the ’triprakoro’ (Notonagoro term), namely customs, culture, and religion. Then with deep thought the ’founding fathers’ made Pancasila the state ideology. Pancasila as the ideology of the Indonesian nation is the work of the Indonesian nation itself, which is parallel to the other major ideologies in the world, it even has advantages over other ideologies. This research method is based on literature research, so the data collected is qualitative data that is processed by reflective method, equipped with the ’verstehen’ method. The results showed that the Pancasila ideology had advantages over the ideology of communism, liberalism and fascism. The Pancasila ideology also has resilience not only because of the internal factors of the ideology itself, namely its amazing unanimity and integrity, but also because of the support of external factors, namely the guardians of the Pancasila ideology, both formal and informal.